The Influence of the CEFR Implementation in ESL Primary Education: Teachers’ Perceptions - Muhamad Abdul Karim, Ashratul Izzati; Binti Sulaiman, Nur Ainil (International Journal of Academic Research in Progressive Education and Development, 2023)
The former curriculum which is the Standard-Based Curriculum for Primary School (KSSR), has undergone a paradigm shift in favour of the recently implemented CEFR-aligned curriculum. Thus, some teachers expressed frustration about their inability to successfully incorporate CEFR-based lesson preparation, teaching, accessing resources, and evaluation techniques into their current teaching style. Therefore, the purpose of this study is to gather opinions from English instructors regarding how they perceive the influence of implementing a CEFR-aligned curriculum on the teaching of English as a Second Language (ESL) in primary schools. There were 150 language teachers from primary schools in one of the cities in Selangor that acts as the respondents of the study. The data was gathered quantitatively utilising a survey questionnaire. Purposive sampling was used to adopt the questionnaire and distribute it to ESL primary school instructors. A descriptive statistic was used to analyse the quantitative data. The findings showed that the majority of the teachers have positive perception with the implementation of CEFR aligned curriculum but the respondents believed that the exposure of the pupils to the CEFR-aligned curriculum were still not enough. Based on the findings, the challenges identified includes non-local textbooks, a lack of training, and insufficient ICT support in teaching & learning materials. Nevertheless, they noticed favourable reactions to the updated CEFR-aligned curriculum. In conclusion, it was suggested that several amendments were made with the CEFR aligned curriculum to ensure the success of our education system.